Production Quantity Estimation Method in Continuous Line Flow and Discontinuous Line Flow Systems with Barchart Simulation - Mhod Razif Idris; Andri Hermawan (Ann Publisher, 2025)
Background. Production quantity forecasting is a crucial element in the planning and control of manufacturing systems, as it directly affects operational efficiency and capacity utilization. Production systems are generally classified into continuous and discontinuous line flow, which differ in process flow characteristics and levels of variability. Aims. This study aims to examine production quantity forecasting methods for both systems using a Barchart simulation approach as a visualization and process time analysis tool. Methods. The research method used is a systematic literature review and conceptual modeling based on production time, cycle time, setup time, and waiting time. Conclusion. The results of the study indicate that Barchart simulation is effective in representing the stability of production flow in continuous line flow systems and identifying process variability and irregularity in discontinuous line flow systems. Implementation. Thus, the Barchart simulation can be used as a simple yet informative tool to support production quantity forecasting based on manufacturing system characteristics.